2021
DOI: 10.1038/s41467-021-21854-5
|View full text |Cite
|
Sign up to set email alerts
|

Global discovery of lupus genetic risk variant allelic enhancer activity

Abstract: Genome-wide association studies of Systemic Lupus Erythematosus (SLE) nominate 3073 genetic variants at 91 risk loci. To systematically screen these variants for allelic transcriptional enhancer activity, we construct a massively parallel reporter assay (MPRA) library comprising 12,396 DNA oligonucleotides containing the genomic context around every allele of each SLE variant. Transfection into the Epstein-Barr virus-transformed B cell line GM12878 reveals 482 variants with enhancer activity, with 51 variants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 130 publications
0
47
0
Order By: Relevance
“…Regulatory Element Locus Intersection (RELI): The RELI algorithm estimated the enrichment of specific genomic features within next generation sequencing datasets, as reported previously [21,56,57]. In addition to comparing pairs of datasets (e.g., two ChIPseq peak sets), RELI systematically estimated the significance of intersections of the genomic coordinates of genetic variants and ChIP-seq peaks, as described previously [21].…”
Section: Methodsmentioning
confidence: 99%
“…Regulatory Element Locus Intersection (RELI): The RELI algorithm estimated the enrichment of specific genomic features within next generation sequencing datasets, as reported previously [21,56,57]. In addition to comparing pairs of datasets (e.g., two ChIPseq peak sets), RELI systematically estimated the significance of intersections of the genomic coordinates of genetic variants and ChIP-seq peaks, as described previously [21].…”
Section: Methodsmentioning
confidence: 99%
“…Therapy with MSCs from healthy donor individuals without relation to genetic variants is increasing in prevalence in SLE. Prior studies have shown the genetic factors contributing to MSC dysfunction in SLE [ 64 – 66 ]. For instance, HLA-DM and HLA-G are identified in SLE [ 67 ] and HLA-G is associated with immunosuppressive property of MSCs [ 68 ].…”
Section: Clinical Applications Of Autologous Vs Allogeneic Mscsmentioning
confidence: 99%
“…A summary of autoimmune disease risk loci used as examples in this review * Transgenic knock-out models of TNFAIP3 also discussed [24,25]. †SNP of interest identified in an MPRA targeted 91 SLE loci [41] Locus Disease(s)…”
Section: Tablementioning
confidence: 99%